ANALYSIS OF STRATEGIES TO IMPROVE EMPLOYEE PERFORMANCE THROUGH THE APPROACH: SKILLS AND ABILITIES, MOTIVATION AND LEADERSHIP - Suma, Dewi (Universitas Pembinaan Masyarakat Indonesia, 2024)
Research background: Human resources as an important component in improving organizational performance require competency development and the granting of authority and responsibility in a planned, directed and strategic manner. This research describes the strategy of BRI Unit Marendal 1 Medan in improving employee performance through an approach to individual characteristics and work discipline. Purpose of the article: Based on the research results, it can be concluded as follows: (1) Strategy for improving employee performance through the approach: (a) Employee Abilities and Skills, that the abilities and skills at BRI Unit Marendal 1 Medan, namely employees, will be directed to what job description employees must carry out. (b) Work Motivation, that work motivation at BRI Unit Marendal 1 Medan is more towards where employees need a job because they have the motivation to earn income and survive. (c) Leadership, leadership at BRI Unit Marendal 1 Medan tends to be a democratic leadership style that involves cultural and communicative values. Methods: This research is field research. This research approach uses a qualitative approach. In this qualitative approach, data is obtained using a comprehensive approach using interviews, direct observation and scientific studies. The data processing techniques in this research are as follows: (a) Predetermined systematics (display), (b) Selecting data that is relevant to the discussion (reduction), (c) Drawing conclusions (conclusion). Findings & value added: The impact of the strategy to improve employee performance through the approach: (a) Compensation, that compensation at BRI Unit Marendal 1 Medan is the compensation given by BRI Unit Marendal 1 Medan to its employees which is quite adequate with the aim of this compensation being able to motivate employees in working and also to welfare of employees. (b) Career, regarding careers at BRI Unit Marendal 1 Medan, career advancement at BRI Unit Marendal 1 Medan is carried out by looking at the extent to which employees are loyal and demonstrate their achievements at work. JEL Classification: L1, M2, L22